Hubungan Gaya Belajar Dan Konsep Diri Terhadap Keterampilan Berpikir Kritis Biologi Peserta Didik Upt Sma Negeri 1 Barru - Afni, Nur (Universitas Muhammadiyah Surabaya, 2025)
Critical thinking skills are important skills in preparing for the challenges of 21st century education. This research aims to determine the relationship between learning styles and self-concept on critical thinking skills of UPT SMA Negeri 1 Barru students. This research was a quantitative study with a correlational design. The research results were analyzed using simple and multiple regression techniques. The results showed 1) learning style affects the critical thinking skills of students as evidenced by a significance value of 0.04 (α < 0.05); 2) self-concept affects the critical thinking skills of students. Self-concept affects the critical thinking skills of students as evidenced by a significance value of 0.00 (α < 0.05); 3) learning styles and self-concept jointly affect the critical thinking skills of students as evidenced by a significance value of 0.001 (α < 0.05); and has an influence of 33.6%. This, it is recommended to educators to pay more attention to learning styles and improving students self-concept in supporting the improvement of students critical thinking skills.